(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Endothelial dysfunction is associated with diabetes mellitus and hypertension. Oxidative stress and augmented activity of associated enzymes like cyclooxygenase (COX) and xanthine oxidase (XO) is a major culprit. In this study, diabetes mellitus (DM) was induced by alloxan (75 mg/kg, i.v) and hypertension was induced by left renal artery (LRA) ligation in male Wistar rats. Treatment with COX inhibitors, etoricoxib (10 mg/kg, p.o), lornoxicam (4.5 mg/kg, i.p) and XO inhibitor, allopurinol (50 mg/kg, p.o) was initiated after confirming induction of diabetes and hypertension and continued for 6 weeks. Vascular reactivity to catecholamines like adrenaline (1 µg/kg), noradrenaline (1 µg/kg), and phenylephrine (1 µg/kg), was evaluated in both models wherein treated rats expressed better responses than untreated groups. In an in vitro study, relaxant response to acetylcholine (ACh) and sodium nitroprusside (SNP) was observed on isolated aortas. Relaxation to ACh was impaired in untreated groups but treated groups produced near to normal relaxant responses. In case of SNP, no significant results were obtained. Diabetes and hypertension induced significant oxidative stress reflected by increase in lipid peroxidation level and decrease in antioxidant enzymes like catalase and superoxide dismutase. Drugs treatment reversed these effects on oxidative stress indices and ameliorated endothelial dysfunction.